The relation of spatio-temporal distribution of landslides to urban development (a case study from the Apulia region, Southern Italy). Issue 4 (28th July 2021) - Zumpano, Veronica; Ardizzone, Francesca; Bucci, Francesco; Cardinali, Mauro; Fiorucci, Federica; Parise, Mario; Pisano, Luca; Reichenbach, Paola; Santaloia, Francesca; Santangelo, Michele; Wasowski, Janusz; Lollino, Piernicola
ABSTRACT: The paper describes the multitemporal landslide inventory map prepared for the urban areas of Motta Montecorvino and Volturino, two municipalities located in the Southern Apennines (Apulia Region, Italy). These territories show a high propensity to landslides of different types and magnitude, which periodically interfere with the anthropic structures and infrastructures. For the study area, the spatial and temporal distribution of landslides is detected for the period between 1954 and 2003, through the visual interpretation of multiple sets of black and white digital stereoscopic aerial photographs at different scales. The analysis reveals locally high frequency of landslide occurrence and built-up areas on existing landslides, either on the body or on the crown areas. In particular, we show that over the years new residential areas were developed despite the presence of large old mass movements.